Patternable production of SrTiO3 nanoparticles using 1-W laser directly on flexible humidity sensor platform based on ITO/SrTiO3/CNT - Duy, Le Thai; Baek, Ji Ye; Mun, Ye Ji; Seo, Hyungtak (Journal of Materials Science and Technology, 2021)
Perovskite oxides like SrTiO3 at the nanoscale are of interest for emerging applications, including high-k dielectrics and sensors. However, their synthesis requires long calcination at the elevated temperature, which is a barrier of their application to flexible electronics. Here, an effective laser-assisted sol-gel method to patternably produce SrTiO3 nanoparticles (∼ 100 nm) in selective areas on polyimide substrates (coated with ITO) is introduced. Importantly, the violet-laser power is just 1 W but sufficient to crystallize the material in a short period (a few seconds). Furthermore, developing a flexible device platform using carbon nanotubes (CNT) and SrTiO3 nanoparticles for detection of humidity changes at room temperature is proposed. The sensor platform has both capacitive and resistive sensing abilities. The resistive mode with a lower power usage (about 0.2 μW) is suitable for long monitoring of humidity in the range of 2% RH and above. The capacitive mode with higher sensitivity, faster response/recovery time (1∼3 min), and lower detection limit (0.5% RH) can be used for calibration purposes. The performance of the flexible sensor is still maintained after 5000 bending cycles at 1.5-cm radius. Altogether, our synthesis method and the flexible sensor show chances for mass-producing perovskite oxides at low cost for wearable electronics.
Keywords: Elevated temperature; Emerging applications; Lower detection limit; Perovskite oxides; Polyimide substrate; Response/recovery time; Sensing abilities; Synthesis method; CNT; Flexible sensor; Laser annealing; Nanoparticles; Patternable; SrTiO3